Effect of black carrot (Daucus carota L.) flour on quality properties and retarding retrogradation by shelf-life of Sulgidduck (rice cake) - Song, Ka-Young; O, Hyeonbin; Zhang, Yangyang; Joung, Ki Youeng; Choi, Dal Woong; Kim, Young-Soon (Progress in Nutrition, 2018)
Black carrot (Daucus carota L.) contains anthocyanins, which are natural pigments that confer a bright red color. It has gained attention as a functional food that reduces the risk of diseases such as diabetes and heart disease and also demonstrates antioxidant activity. The goal of the present study was to identify the optimal proportion of black carrot flour for use in Sulgidduck (rice cake) in order to achieve high quality and retard retrogradation or tendency to become stale. Sulgidduck was prepared by replacing 0%, 0.5%, 1%, 2%, 3%, and 4% of the rice flour with black carrot flour; these preparations were designated as the control (without BC flour), BC0.5, BC1, BC2, BC3, and BC4.